Elevations of N-Terminal Mid-Fragment of Osteocalcin and Cystatin C Levels are Associated with Disorders of Glycolipid Metabolism and Abnormal Bone Metabolism in Patients with Type 2 Diabetes Mellitus Complicated with Osteoporosis - Xiaofang Guo; Yun Shen; Teng Du; Yan He; Jie Lu; Qianhong Yang (Journal of Physiological Investigation)
Type 2 diabetes mellitus (T2DM) patients always develop osteoporosis (OP). We examined correlations of N-terminal mid-fragment of osteocalcin (N-MID) and cystatin C (Cys C) levels with glycolipid metabolism, bone metabolism markers, and bone mineral density (BMD) in elderly T2DM-OP patients. Grouping was performed as per whether T2DM patients developed OP (OP group) or not (N-OP group). N-MID and Cys C were measured using enzyme-linked immunosorbent assay, with correlations with glycolipid metabolism, bone metabolism indicators, and BMD analyzed using Pearson’s correlation coefficient. Elderly T2DM-OP patients showed elevated disease duration, age, body mass index, glycated hemoglobin (HbA1c), Homer’s insulin resistance (HOMA-IR), total cholesterol (TC), beta-carboxy-terminal crosslinked telopeptide of type 1 collagen (β-CTX), tartrate-resistant acid phosphatase 5b (TRACP-5b), N-MID and Cys C levels, and reduced high-density lipoprotein cholesterol (HDL-C), bone alkaline phosphatase (B-ALP), aminoterminal propeptide of type I procollagen (PINP), carboxyterminal propeptide of type I procollagen (PICP), BMD, and calcium supplementation. N-MID and Cys C were positively correlated with HbA1c, HOMA-IR, TC, β-CTX, and TRACP-5b and negatively with HDL-C, B-ALP, PINP, PICP, and BMD in elderly T2DM-OP patients. Conclusively, the abnormal elevations of serum N-MID and Cys C were associated with glycolipid metabolism disorder, abnormal bone metabolism, and decreased BMD in elderly T2DM-OP patients.